INTERELASI HINDU DENGAN BUGIS: MENGGALI AJARAN SANATANA DHARMA DALAM KEPERCAYAAN TOLOTANG - Sugiarti Sugiarti (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Tolotang or Towani Tolotang is a Hindu community found in South Sulawesi. This community is part of the Bugis ethnicity, but there are differences with Bugis in general, because it still maintains old beliefs. This belief is similar to the teachings influenced by Hinduism, which developed in the Indonesian archipelago, especially in the use of offerings in rituals. The mention of the Supreme Deity, Dewata Seuwae also bears a resemblance to the god Shiva in Hinduism, the terms Batara Guru, Sangiang or Sangeng Serri, pèrètiwi are deities contained in Hinduism. Although at the level of tradition, Tolotang is different from Bali and India, but in essence contains similarities. His recognition of being a Hindu is not solely to maintain the existence and recognition of the state, but also to use Hinduism as a "spirit" in developing and maintaining his "Tolotang". The differences in Tolotang's traditions and customs from Bali, India, and other areas that were once influenced by Hinduism were not to be polemic, because these differences were mostly on the "casing" level. Differences in customs and traditions are natural, given the Ashwalayana Grihyasuta Book also advocates this; there are various customs that apply in this world, both in the villages or in cities, all of which must be carried out in accordance with the generally accepted customs in the place. This study shows that there is a relationship between the teachings of Sanatana Dharma or Hinduism in Tolotang beliefs. The recognition of the Tolotang community as adherents of Sanatana Dharma is basically giving guidance to Towani Tolotang to better understand the teachings of its parent, namely Sanatana Dharma.